H i constraints from the cross-correlation of eBOSS galaxies and Green Bank Telescope intensity maps. Issue 3 (13th December 2021) - Wolz, Laura; Pourtsidou, Alkistis; Masui, Kiyoshi W; Chang, Tzu-Ching; Bautista, Julian E; Müller, Eva-Maria; Avila, Santiago; Bacon, David; Percival, Will J; Cunnington, Steven; Anderson, Chris; Chen, Xuelei; et al.
ABSTRACT: We present the joint analysis of Neutral Hydrogen (H i ) Intensity Mapping observations with three galaxy samples: the Luminous Red Galaxy (LRG) and Emission Line Galaxy (ELG) samples from the eBOSS survey, and the WiggleZ Dark Energy Survey sample. The H i intensity maps are Green Bank Telescope observations of the redshifted $21\rm cm$ emission on $100 \, {\rm deg}^2$ covering the redshift range 0.6 < z < 1.0. We process the data by separating and removing the foregrounds present in the radio frequencies with FastI ICA . We verify the quality of the foreground separation with mock realizations, and construct a transfer function to correct for the effects of foreground removal on the H i signal. We cross-correlate the cleaned H i data with the galaxy samples and study the overall amplitude as well as the scale dependence of the power spectrum. We also qualitatively compare our findings with the predictions by a semianalytical galaxy evolution simulation. The cross-correlations constrain the quantity $\Omega _{\rm {H\, \small {I}}} b_{\rm {H\, \small {I}}} r_{\rm {H\, \small {I}}, {\rm opt}}$ at an effective scale k eff, where $\Omega _\rm {H\, \small {I}}$ is the H  i density fraction, $b_\rm {H\, \small {I}}$ is the H i bias, and $r_{\rm {H\, \small {I}}, {\rm opt}}$ the galaxy–hydrogen correlation coefficient, which is dependent on the H  i content of the optical galaxy sample. At $k_{\rm eff}=0.31 \, h\, {\rm Mpc^{-1}}$ we find $\Omega _{\rm {H\, \small {I}}} b_{\rm {H\, \small {I}}} r_{\rm {H\, \small {I}}, {\rm Wig}} = [0.58 \pm 0.09 \, {\rm (stat) \pm 0.05 \, {\rm (sys)}}] \times 10^{-3}$ for GBT-WiggleZ, $\Omega _{\rm {H\, \small {I}}} b_{\rm {H\, \small {I}}} r_{\rm {H\, \small {I}}, {\rm ELG}} = [0.40 \pm 0.09 \, {\rm (stat) \pm 0.04 \, {\rm (sys)}}] \times 10^{-3}$ for GBT-ELG, and $\Omega _{\rm {H\, \small {I}}} b_{\rm {H\, \small {I}}} r_{\rm {H\, \small {I}}, {\rm LRG}} = [0.35 \pm 0.08 \, {\rm (stat) \pm 0.03 \, {\rm (sys)}}] \times 10^{-3}$ for GBT-LRG, at z ≃ 0.8. We also report results at $k_{\rm eff}=0.24$ and $k_{\rm eff}=0.48 \, h\, {\rm Mpc^{-1}}$ . With little information on H i parameters beyond our local Universe, these are amongst the most precise constraints on neutral hydrogen density fluctuations in an underexplored redshift range.